The Ballad of Renoviction - Kargotis, Demetrios; Mortimer, Nicholas; Macdonald, Dash; Dahlqvist, Sebastian (My University, 2024)
The Ballad of Renoviction is a site-specific performance developed by Post Workers Theatre as part of Stockholm City Blues, a public theatre work staged in Hägersten, Stockholm. The performance engages with the legacy of Spelet om Hägersten, a community workers’ play from the 1970s–80s, to examine contemporary processes of housing privatization, displacement, and urban transformation. The work was developed over a five-month period through a process of practice-based research involving collaboration with Hägerstensåsens Medborgarhus and artist Sebastian Dahlqvist (Royal Institute of Art, Stockholm). Drawing on materials from the Swedish Labour Movement’s Archive and Library, the project enabled a cross-cultural exchange of ideas between English and Swedish histories of workers’ theatre. Using accessible folk theatre and collective storytelling, the performance situates audiences within the changing urban fabric of Stockholm, foregrounding the social consequences of neoliberal housing policy and activating public space as a site of critical reflection and civic engagement.
Stockholm City Blues – Scene 2: The Ballad of Renoviction
Keywords: Performance